Understanding the Molecular Mechanisms that Contribute to Parkinson’s Disease: Defining the Role of Ca2+ in TG2: α-synuclein Macromolecular Complex Assembly - Washington, James (East Carolina University, 2018)
Transglutaminase 2 (TG2) is an allosteric enzyme ubiquitously expressed in human tissue. This versatile enzyme has both Ca2+ -dependent, transamidase and GTPase activities. TG2's Ca2+ -dependent transamidase activity is linked to many different diseases; most notably neurodegenerative diseases like Parkinson's. Initial Ca2+-dependent, TG2 mediated post-translational modification of pathogenic proteins - including [alpha]-synuclein, tau, and [beta]-amyloid--increases their aggregations potential. As the disease progresses, neuronal damage causes a loss of Ca2+ homeostasis (i.e. increasing intracellular Ca2+ concentrations) and further activation of TG2; these increased activities further facilitate the formation of pathogenic protein oligomers. As such, the exacerbated symptoms of neurodegenerative disease can, in part, be attributed to this destructive cycle. The allosteric mechanism by which Ca2+ controls TG2's transamidase activity is not fully understood. The currently accepted model posits that Ca2+ binding to TG2 prior to the protein substrate (i.e. [alpha]-synuclein) induces conformational changes necessary for substrate binding and catalytic turnover. However, our preliminary data, using [alpha]-synuclein as a model substrate, challenges this theory; our model indicates that Ca2+ binding occurs after enzyme-substrate complex formation. That is, Ca2+ activates the TG2: [alpha]-synuclein complex. In light of this data, we aim to answer the question "What role does Ca2+ have in activating of the TG2: substrate complex?" We hypothesize that Ca2+ binding to the complex increases the stability of the enzyme: substrate complex, thereby increasing the rate of catalysis. Using Surface Plasmon Resonance (SPR), we have shown that the interactions between TG2 and [alpha]-synuclein do not adhere to a simple 1:1 binding model; as such, possible binding models for macromolecular complex formation are presented. We have also identified potential Ca2+- binding regions on TG2 using multiple alignments. We expect our findings will be beneficial in developing an accurate model for TG2 activation, which can further be used to develop therapeutics that inhibit activity.
Keywords: TG2; Parkinson Disease; Transglutaminases; Biological Phenomena; alpha-Synuclein